2022
DOI: 10.3389/fonc.2022.904563
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Field Doses Produced by a Proton Scanning Beam Inside Pediatric Anthropomorphic Phantoms and Their Comparison With Different Photon Modalities

Abstract: Since 2010, EURADOS Working Group 9 (Radiation Dosimetry in Radiotherapy) has been involved in the investigation of secondary and scattered radiation doses in X-ray and proton therapy, especially in the case of pediatric patients. The main goal of this paper is to analyze and compare out-of-field neutron and non-neutron organ doses inside 5- and 10-year-old pediatric anthropomorphic phantoms for the treatment of a 5-cm-diameter brain tumor. Proton irradiations were carried out at the Cyclotron Centre Bronowice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…In all cases investigated by WG9 out-of-field organ doses were assessed inside anthropomorphic phantoms for the same target (6 cm diameter spherical PTV with the center on the left anterior side of the head). This work was recently summarized by Knezevic et al ( 2022 ). Table 1 presents example data for out-of-field dose levels estimated by EURADOS WG9 for 3D-CRT, IMRT (Majer et al 2017 ) and Intensity Modulated Proton Therapy (IMPT) with PBS technique (Knezevic et al 2018 ).…”
Section: Out-of-field Effects: Clinical Contextmentioning
confidence: 86%
See 1 more Smart Citation
“…In all cases investigated by WG9 out-of-field organ doses were assessed inside anthropomorphic phantoms for the same target (6 cm diameter spherical PTV with the center on the left anterior side of the head). This work was recently summarized by Knezevic et al ( 2022 ). Table 1 presents example data for out-of-field dose levels estimated by EURADOS WG9 for 3D-CRT, IMRT (Majer et al 2017 ) and Intensity Modulated Proton Therapy (IMPT) with PBS technique (Knezevic et al 2018 ).…”
Section: Out-of-field Effects: Clinical Contextmentioning
confidence: 86%
“…For 3D-CRT, IMRT and proton active scanning radiotherapy data are adapted from Knezevic et al ( 2022 ). For passive scattering proton radiotherapy data are adapted from Sayah et al ( 2014 ) assuming 10% contribution from secondary photons to total organ equivalent dose.…”
Section: Out-of-field Effects: Clinical Contextmentioning
confidence: 99%
“…14 The study found a decreased total organ dose equivalent for intensity modulated proton therapy (IMPT) with pencil beam scanning compared to photon therapy. 14 Compared to phantom measurements taken with bubble detectors at the Indiana University Cyclotron double scattering system, reported by Mesoloras et al, the fetal dose is reduced from the 25-871 µSv per Gy to the maximum 64.7 µSv per 2 Gy(RBE) reported here. 15 With previous literature demonstrating that passively scattered proton therapy is not associated with a significant increase in secondary malignancies when compared with photon therapy, 3,16 our work suggests that this risk is further reduced when using pencil beam scanning systems, such as the Mevion S250i system.…”
Section: Discussionmentioning
confidence: 99%
“…Additional work by Knežević et al. demonstrated the differences in dose for proton therapy compared to 3D conformal radiation therapy, IMRT, and Gamma Knife (Elekta, Stockholm, Sweden) with the proton therapy plan containing two coplanar beams treating a brain lesion in a pediatric phantom 14 . The study found a decreased total organ dose equivalent for intensity modulated proton therapy (IMPT) with pencil beam scanning compared to photon therapy 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation